Foods for Special Dietary Regimens - Pérez, Elevina E. (Bentham Science Publishers, 2021)
Foods for Special Dietary Regimens is an overview of alimentation for people with specific medical conditions. Each of the nine featured chapters describes a recommended diet with special reference to the lifestyle or disease conditions in a specific patient group. The book covers a diverse range of patient groups that have special nutritional requirements including the elderly, athletes, vegetarians, diabetics and phenylketonurics to name a few. Diets for individuals affected by specific diseases such as celiac disease, autism, dyslipidemia, and COVID-19 are also recommended. Readers will gain a broad perspective about special dietary regimens, including information about what works and what does not for different patient groups, and potential avenues of research in this area.Key Features:- 9 chapters organized into a simple reader-friendly format- guidelines for patient groups on lifestyle- information for patient groups based on different clinically relevant diseases (including COVID-19)- information about general concepts and clinical research- references for further reading